A rare polyglycine type II‐like helix motif in naturally occurring proteins. Issue 11 (4th August 2017) - Warkentin, Eberhard; Weidenweber, Sina; Schühle, Karola; Demmer, Ulrike; Heider, Johann; Ermler, Ulrich
Abstract: Common structural elements in proteins such as α‐helices or β‐sheets are characterized by uniformly repeating, energetically favorable main chain conformations which additionally exhibit a completely saturated hydrogen‐bonding network of the main chain NH and CO groups. Although polyproline or polyglycine type II helices (PPII or PGII ) are frequently found in proteins, they are not considered as equivalent secondary structure elements because they do not form a similar self‐contained hydrogen‐bonding network of the main chain atoms. In this context our finding of an unusual motif of glycine‐rich PGII ‐like helices in the structure of the acetophenone carboxylase core complex is of relevance. These PGII ‐like helices form hexagonal bundles which appear to fulfill the criterion of a (largely) saturated hydrogen‐bonding network of the main‐chain groups and therefore may be regarded in this sense as a new secondary structure element. It consists of a central PGII ‐like helix surrounded by six nearly parallel PGII ‐like helices in a hexagonal array, plus an additional PGII ‐like helix extending the array outwards. Very related structural elements have previously been found in synthetic polyglycine fibers. In both cases, all main chain NH and CO groups of the central PGII ‐helix are saturated by either intra‐ or intermolecular hydrogen‐bonds, resulting in a self‐contained hydrogen‐bonding network. Similar, but incomplete PGII ‐helix patterns were also previously identified in a GTP‐binding protein and an antifreeze protein.